COMPARATIVE ANALYSIS OF DIFFERENCES IN EXHIBITING FLEXIBILITY IN YOUNG FOOTBALL PLAYERS AND KARATE PRACTITIONERS (KARATEKA) - Enes Šunje; Čolakhodžić Ekrem; Rijad Novaković; Alić Džafer; Redžić Enaid (Sport Scientific And Practical Aspects, 2025)
The athlete’s ability to achieve the maximum amplitude of movement in certain sports can be crucial for achieving a top result. Most theorists consider flexibility to be one of the essential motor skills of humans. Flexibility is defined as the ability of the locomotor apparatus to realize movements of optimal amplitude in a certain joint. The goal of this research was to determine the differences in flexibility between football players and karate practitioners (karateka) between the ages of 12 and 14 years, in chronological order. The purpose of this paper is to determine the differences in flexibility between football players and karateka based on the obtained results, and to further determine whether and within which variables of flexibility karateka are more dominant than football players. This research will complete the findings and fill the knowledge gaps that exist about flexibility. The importance of this research is reflected in that it will gather relevant information about the status and differences in flexibility between football players and karateka within the specified age group. The research was carried out on a sample of 40 respondents who make up two subsamples, football players (n=20; age 12.70 ± 0.86) and karateka (n=20; age 12.95 ± 0.82). Tests were applied to determine height and body mass, as well as to determine flexibility (10 variables). The obtained results were processed in the program package IBM SPSS Statistics 26.0. Descriptive parameters were calculated for all collected data, normality of distribution was determined, while differences in tests were determined by T-test for independent samples. The results showed that in terms of body height and mass, there are no statistically significant differences between young football players and karateka, nor in the ability to lower a stick behind the back (MFLISK). In all other flexibility tests (deep front bend off an elevated platform/block, deep bend with legs apart, side split, active straight leg raise while lying on the back (degrees) for both legs, leg raises while lying on the chest, leg raise while lying on the side) a statistically significant difference was obtained at the significance level of .99% (p ≤ 0.01), and all in favor of karateka. We can conclude that the level of flexibility is higher in karate practitioners compared to football players, which was to be expected. The main discovery of this study is the existence of statistically significant differences in almost all flexibility variables, where better values were shown in favor of karatekas, except for the back stick raise test, where no statistically significant difference was found between football players and karateka. The research can serve other researchers who will deal with similar issues, and the findings of this research will complete the mosaic of research regarding flexibility in karate and football. The obtained results will benefit sports teams, researchers, trainers and physical education professors, as a relevant indicator of the importance and significance of flexibility development and flexibility training in sports.